Neoadjuvant atezolizumab and chemotherapy in patients with resectable non-small-cell lung cancer: an open-label, multicentre, single-arm, phase 2 trial. Issue 6 (June 2020) - Shu, Catherine A; Gainor, Justin F; Awad, Mark M; Chiuzan, Codruta; Grigg, Claud M; Pabani, Aliyah; Garofano, Robert F; Stoopler, Mark B; Cheng, Simon K; White, Abby; Lanuti, Michael; D'Ovidio, Frank; et al.
Summary: Background: Approximately 25% of all patients with non-small-cell lung cancer present with resectable stage IB–IIIA disease, and although perioperative chemotherapy is the standard of care, this treatment strategy provides only modest survival benefits. On the basis of the activity of immune checkpoint inhibitors in metastatic non-small-cell lung cancer, we designed a trial to test the activity of the PD-L1 inhibitor, atezolizumab, with carboplatin and nab-paclitaxel given as neoadjuvant treatment before surgical resection. Methods: This open-label, multicentre, single-arm, phase 2 trial was done at three hospitals in the USA. Eligible patients were aged 18 years or older and had resectable American Joint Committee on Cancer-defined stage IB–IIIA non-small-cell lung cancer, an Eastern Cooperative Oncology Group performance status of 0–1, and a history of smoking exposure. Patients received neoadjuvant treatment with intravenous atezolizumab (1200 mg) on day 1, nab-paclitaxel (100 mg/m 2 ) on days 1, 8, and 15, and carboplatin (area under the curve 5; 5 mg/mL per min) on day 1, of each 21-day cycle. Patients without disease progression after two cycles proceeded to receive two further cycles, which were then followed by surgical resection. The primary endpoint was major pathological response, defined as the presence of 10% or less residual viable tumour at the time of surgery. All analyses were intention to treat. This study is registered with ClinicalTrials.gov, NCT02716038, and is ongoing but no longer recruiting participants. Findings: Between May 26, 2016, and March 1, 2019, we assessed 39 patients for eligibility, of whom 30 patients were enrolled. 23 (77%) of these patients had stage IIIA disease. 29 (97%) patients were taken into the operating theatre, and 26 (87%) underwent successful R0 resection. At the data cutoff (Aug 7, 2019), the median follow-up period was 12·9 months (IQR 6·2–22·9). 17 (57%; 95% CI 37–75) of 30 patients had a major pathological response. The most common treatment-related grade 3–4 adverse events were neutropenia (15 [50%] of 30 patients), increased alanine aminotransferase concentrations (two [7%] patients), increased aspartate aminotransferase concentration (two [7%] patients), and thrombocytopenia (two [7%] patients). Serious treatment-related adverse events included one (3%) patient with grade 3 febrile neutropenia, one (3%) patient with grade 4 hyperglycaemia, and one (3%) patient with grade 2 bronchopulmonary haemorrhage. There were no treatment-related deaths. Interpretation: Atezolizumab plus carboplatin and nab-paclitaxel could be a potential neoadjuvant regimen for resectable non-small-cell lung cancer, with a high proportion of patients achieving a major pathological response, and manageable treatment-related toxic effects, which did not compromise surgical resection. Funding: Genentech and Celgene.